Clinical studies of NM441 in urinary tract infection - Muranaka, Koji; Okada, Kenichiro (Japanese Journal of Chemotherapy, 1996)
We evaluated the clinical efficacy and safety of NM441, a new quinolon derivative, in patients with urinary tract infections (UTI). Two patients with acute uncomplicated cystitis (AUC), 8 patients with complicated UTI and one patient with acute epididymitis were treated with NM441. According to the criteria proposed by the Japanese UTI Committee, the overall clinical efficacy was 2/2 in AUC, 6/8 in complicated UTI and 1/1 in acute epididymitis. All 2 strains of Escherichia coli and 1 strain of Enterococcus faecalis were eradicated in AUC. Although 1 strain of Staphylococcus aureus persisted, all other bacteria (2 strains of Staphylococcus epidermidis, 2 strains E. coli, 1 strain of Enterobacter aerogenes, 1 strain of E. faecalis and 1 strain of Serratia marcescens) were eradicated in complicated UTI. There were no significant clinical and laboratory adverse reaction. We conclude that NM441 is an effective and safe agent for UTI.